A ilustração do espírito: o discurso político da Revista Illustrada (1876-1898) - Guilherme Elias de Figueiredo (2014)
This research analyzes the political discourse of the brazilian illustrated magazine called Revista Illustrada between the years 1876 and 1898. Our intention is to demonstrate that discourse of this magazine is a form of political action established by discussion with intellectuals and journalists from Brazil at the end of nineteenth-century. The main hypothesis of the analysis is that the discursive core of the Revista Illustrada was a free appropriation of republican ideals by its editors and contributors. We investigate how the ideas were manifested in texts and caricatures from the periodic. Our analysis considered the editorial design from Revista Illustrada with regard to aspects of its materiality, the dynamics of development, production and distribution. The aim was to understand the space of this magazine in brazilian society of nineteenth-century for an approach that made questions about historical and linguistic context and the interactions established among its employees and other members of the press.The selected historical period covers two moments for politics and press in Brazil: the first moment happens prior to the proclamation of the republic, between 1876 and 1889, and was marked by the crisis of the monarchy and the emergence of numerous political projects that were discussed in the press of court. In this phase the Revista Illustrada was directed by italo-brazilian cartoonist Angelo Agostini who established an intense debate with other journals from Brazil to defend political causes as the end of the of slavery. The research concentrated on analyzing this period, when was consolidated the discursive framework of this magazine. The second moment refers to the early years of the brazilians republic, between 1889 and 1898. In this context, we perceived that government acted to contain the discourses of opposition in the press. Many journals had to rethink their positions, converging to unconditional support of members of political. In this case we examined the posture review from the magazine inside this new scenario for brazilian newspapers. We note that the study of political discourse Revista Illustrada helps to thinking about the role and posture of the press on changes in Brazil in the late nineteenth-century, confirming the need to consider the motion and the ways that political ideas gained in this particular historical and linguistic context.